The whole idea is to get x or y itself from one equation and plug it into the second equation, so the second will have only one variable. Let's get y itself from the first equation:9x-58=8y. Divide both sides by 8: 9/8(x)-58/8=y. Now in the second equation replace y by 9/8(x)-58/8. -5x+4(9/8(x)-58/8)=-30. Simplify:-5x+9/2(x)-58/2=-30. -5x+4.5x-29=-30. -0.5x-29=-30. -0.5x=-1. x=2. Plug x=2 into one of equations to get y; let's use the first one; 9*2-58=8y; 18-58=8y; -40=8y: y=-5!!! So x=2, y=-5 or (2,-5)